A prospective evaluation of the feasibility of using enrolled nursing auxiliaries to triage patients in the emergency unit of an urban public hospital in South Africa - Bruins, Stevan Raynier (Division of Emergency Medicine, 2014)
Includes bibliographical references (leaves 73-80).